Evaluation of structural properties of cylindrical packed beds using numerical simulations and tomographic experiments - Mariani, Nestor Javier (2009)
This contribution is focused on the analysis of the structure of packed beds of spherical particles at relatively low aspect ratios (i.e., particle to tube diameter ratio) as those arising in multitubular fixed bed reactors. On one hand, the computed tomography (CT) technique is employed to evaluate the position of each particle in the packing and from this information local properties such as particle center distribution and radial porosity profile were obtained. On the other hand, results from a previously developed algorithm to simulate packings were compared with those from our CT data and from literature sources. The agreement was very satisfactory.